(untitled) (Research, Society and Development, 2023)
A standing oral examination under sedation in horses is essential to facilitate the handling and ensure an excellent examination. This study aimed to determine if the use of diazepam associated with detomidine would increase the action of the α2 agonist (detomidine), mainly by tongue motion and chewing reduction without excessive destabilization. Twelve adult horses of different age, breed and gender underwent dental correction. The animals were randomly assigned to two treatments: detomidine (20 µg.kg-1, IV) and diazepam (20 µg.kg-1, IV) (DD; n=6) or detomidine (20 µg.kg-1, IV) and 0.9% NaCl (DS; n=6). Tongue relaxation and exposure, heart rate, PR interval, respiratory rate, systolic blood pressure, rectal temperature, second-degree atrioventricular blocks, degree of ataxia and head movement were assessed at nine separated time points. Height of head above ground (HHAG) was assessed at three separate times. Detomidine rescue (5µg.kg-1, IV) was administered whenever a sedation increase was needed. All treatments provided adequate sedation and muscle relaxation. Differences between time points were observed for tongue relaxation (tongue VAS mm) and this was best observed at T7 for the DD treatment and T5 for the DS treatment and remained significantly lower than baseline throughout the times assessed. It was concluded that detomidine provided adequate sedation in horses undergoing dental examination, but there was no significant difference between treatments for any variable studied. The addition of diazepam did not improve the sedation or reduce the tongue movement.